2012
DOI: 10.1177/0003319711421164
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Colorectal Cancer

Abstract: The effect of Mediterranean diet on colorectal cancer, in the presence of the metabolic syndrome, was evaluated in 250 patients with first developed cancer (63 ± 12 years, 59% males) and 250 age-gender-matched controls. Adherence to the Mediterranean diet was evaluated with the modified-MedDietScore (theoretical range 0-75), while assessment of the metabolic syndrome (MetS) was based on the third Adult Treatment Panel ([ATP III] National Cholesterol Education Program) criteria. Presence of MetS (1.66, 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Combining the three Italian studies, the highest adherence to the MD compared with the lowest reduced colorectal cancer risk by about 50%, consistent across the large bowel. We found a stronger inverse association between MD and colorectal cancer than that reported in a Greek case–control study (OR 0.88; Kontou et al , 2012 ) but similar to that found in an Italian case–control study (OR 0.46; Grosso et al , 2014 ) and an Italian cohort study (hazard ratio 0.50; Agnoli et al , 2013 ) and stronger than that found in a meta-analysis (pooled relative risk of 0.86; Schwingshackl and Hoffmann, 2014 ). However, comparison between studies is difficult because of the differences of dietary habits between various countries, the use of different components and cut points in the MD definition, and the different prevalence of adherence to the MD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Combining the three Italian studies, the highest adherence to the MD compared with the lowest reduced colorectal cancer risk by about 50%, consistent across the large bowel. We found a stronger inverse association between MD and colorectal cancer than that reported in a Greek case–control study (OR 0.88; Kontou et al , 2012 ) but similar to that found in an Italian case–control study (OR 0.46; Grosso et al , 2014 ) and an Italian cohort study (hazard ratio 0.50; Agnoli et al , 2013 ) and stronger than that found in a meta-analysis (pooled relative risk of 0.86; Schwingshackl and Hoffmann, 2014 ). However, comparison between studies is difficult because of the differences of dietary habits between various countries, the use of different components and cut points in the MD definition, and the different prevalence of adherence to the MD.…”
Section: Discussionsupporting
confidence: 82%
“…A meta-analysis of five cohort and two case–control studies reported a statistically significant 14% reduction of colorectal cancer risk, similar for cohort and case–control studies ( Schwingshackl and Hoffmann, 2014 ). However, only three studies were conducted in countries with typical MD: a Greek ( Kontou et al , 2012 ) and an Italian ( Grosso et al , 2014 ) case–control studies and an Italian cohort study ( Agnoli et al , 2013 ), part of the European Prospective Investigation into Cancer and Nutrition ( Bamia et al , 2013 ).…”
mentioning
confidence: 99%
“…Physical activity, omega-3 fatty acids and some diets appear to confer some protection. Some trials have consistently showed that a Mediterranean diet can lead to regression of MetS and have a protective role regarding the development of CRC [ 32 , 33 ]. Other possible adverse influence of DM or hypertension on CRC prognosis may be counterbalanced by potential protective effects of some medications, such as Metformin [ 34 ], antagonism of beta-adrenergic signaling [ 35 ] and statins [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four prospective cohort studies [ 20 , 54 56 ] and four case–control studies [ 19 , 57 59 ] investigated the effects of adherence to MD and risk of colorectal cancer. Of these eight studies, two cohort and three case–control studies demonstrated a significant inverse association between adherence to MD and incidence of colorectal cancer.…”
Section: Cancer Localizationsmentioning
confidence: 99%